1990
DOI: 10.1021/ac00212a023
|View full text |Cite
|
Sign up to set email alerts
|

Square-wave anodic stripping voltammetry at glassy-carbon-based thin mercury film electrodes in solutions containing dissolved oxygen

Abstract: Square-wave anodic stripping voltammetry (SWASV) of nanomolar concentration levels of lead and calcium at glassycarbon-based thin mercury film electrodes was Investigated In the presence of dissolved oxygen. Anodic stripping measurements In nondeaerated solutions were possible because of the depletion of oxygen at the electrode surface prior to the stripping step and because of the fast-scanning ability of square-wave voltammetry, which allows for the completion of the stripping step before any significant oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

1991
1991
2006
2006

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 6 publications
1
30
0
1
Order By: Relevance
“…Earlier, Wojciechowski and Balcerzak [9], using square wave voltammetry, compared the analytical results for Pb and Cd in untreated tap water samples obtained with and without deaeration. They found that good results could be obtained without removing oxygen from the sample.…”
Section: Effect Of the Presence Of Oxygenmentioning
confidence: 99%
“…Earlier, Wojciechowski and Balcerzak [9], using square wave voltammetry, compared the analytical results for Pb and Cd in untreated tap water samples obtained with and without deaeration. They found that good results could be obtained without removing oxygen from the sample.…”
Section: Effect Of the Presence Of Oxygenmentioning
confidence: 99%
“…Other recent studies in natural waters have illustrated the portability of voltammetric techniques for the in situ measurement of trace metals, while maintaining excellent analytical performance [69]. Potentiometric (SWASV) has been used successfully for the determination of trace lead and cadmium in untreated water samples at MFEs [75] and mercury-coated microelectrodes [76]. No deaeration of dissolved oxygen was required, even though the water samples were air-saturated.…”
Section: Heavy Metal Analysismentioning
confidence: 99%
“…In this case oxygen reduction does not yield differential current and thus background correction is not necessary [18]. Since Hg is not soluble in Pt, the thickness of the mercury film can be kept much smaller to increase the sensitivity and lower the detection limit.…”
Section: Stripping Analysis With a Platinum Electrodementioning
confidence: 99%